Evolution of the androgen receptor: Perspectives from human health to dancing birds. (1st January 2020) - Schuppe, Eric R.; Miles, Meredith C.; Fuxjager, Matthew J.
Abstract: Androgenic hormones orchestrate the development and activation of diverse reproductive phenotypes across vertebrates. Although extensive work investigates how selection for these traits modifies individual elements of this signaling system (e.g., hormone or androgen receptor [AR] levels), we know less about natural variation in the AR sequence across vertebrates. Our knowledge of AR sequence mutations is largely limited to work in human patients or cell-lines, providing a framework to contextualize single mutations at the expense of evolutionary timescale. Here we unite both perspectives in a review that explores the functional significance of AR on a domain-by-domain basis, using existing knowledge to highlight how and why each region might evolve. We then examine AR sequence variation on different timescales by examining sequence variation in clades originating in the Cambrian (vertebrates; >500 mya) and Cretaceous (birds; >65 mya). In each case, we characterize how the receptor has changed over time and discuss which regions are most likely to evolve in response to selection. Overall, domains that are required for androgenic signaling to function (e.g., DNA- and ligand-binding) tend to be conserved. Meanwhile, areas that interface with co-regulatory molecules can exhibit notable variation even between closely related species. We propose that accumulating mutations in regulatory regions is one way that AR structure might act as a substrate for selection to guide the evolution of reproductive traits. By synthesizing literature across disciplines and highlighting the evolutionary potential of specific AR regions, we hope to inspire new avenues of integrative research into endocrine system evolution. Highlights: AR expression is highly conserved in regions that interact with DNA and bind ligands. AR is less conserved in regions that interact with regulatory proteins. Domain-specific evolution may occur to support adaptation of androgenic traits. This may have occurred in birds, including manakins, hummingbirds, and pelicans.